An intro to learning Apache Hadoop - Morrow, Rich; Safari eBooks ([Place of publication not identified] : O'Reilly, 2015)
"In this fast-paced, interactive, info-rich webcast led by Rich Morrow, we'll discuss: the value proposition of Hadoop, common use cases, how to run it on premises and in the cloud via AWS EMR."--Resource description page.
Presenter, Rich Morrow.
Title from title screen (viewed, September 29, 2015)
Date of publication from resource description page.
Keywords: Apache Hadoop; Electronic data processing -- Distributed processing; Cloud computing; File organization (Computer science); Electronic books